Knowledge of HIV/AIDS Among Adolescents in Indonesia: A Systematic Review - Alwi, M Akbar; Hamzah, Hadzmawaty; Syarifuddin, Surya; Karlina, Lilis (Faculty of Medicine, Universitas Tadulako, 2025)
Background: HIV/AIDS remains a significant public health issue globally, with adolescents being one of the most at-risk groups due to various risky behaviors. Limited access to comprehensive information contributes to the continued transmission of HIV within this age group. Objectives: This study aims to describe the level of knowledge about HIV/AIDS among adolescents in Indonesia. Methods: A systematic review was conducted by examining articles published between 2010 and 2024 that align with the study objectives. Ten relevant studies were identified and analyzed. Results: Among the studies reviewed, four reported that adolescent knowledge of HIV/AIDS was categorized as